2016
DOI: 10.1002/hep.28506
|View full text |Cite
|
Sign up to set email alerts
|

Atorvastatin and fluvastatin are associated with dose‐dependent reductions in cirrhosis and hepatocellular carcinoma, among patients with hepatitis C virus: Results from ERCHIVES

Abstract: Background Statins are associated with delayed fibrosis progression and a reduced risk of hepatocellular carcinoma (HCC) in chronic hepatitis C virus (HCV). Limited data exist regarding the most effective type and dose of statin in this population. We sought to determine the impact of statin type and dose upon fibrosis progression and HCC, in patients with HCV. Methods Using the Electronically Retrieved Cohort of HCV Infected Veterans (ERCHIVES) database, we identified all subjects initiated on anti-HCV ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
168
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(179 citation statements)
references
References 52 publications
6
168
0
5
Order By: Relevance
“…Of the 1706 unique studies identified using our search criteria, 13 studies met our inclusion criteria and were included in our meta-analysis (3 RCTs and 10 observational studies) 3343, 50, 51 Six studies included participants with non-cirrhotic CLDs 35, 3943 , six studies included participants with compensated cirrhosis 36, 37, 42, 43, 50, 51 , and three studies included individuals with decompensated cirrhosis 33, 34, 38 . One study was excluded as it represented a population already included in another, more recent study; 52 one small RCT of statins in NASH was excluded due to insufficient information 53 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the 1706 unique studies identified using our search criteria, 13 studies met our inclusion criteria and were included in our meta-analysis (3 RCTs and 10 observational studies) 3343, 50, 51 Six studies included participants with non-cirrhotic CLDs 35, 3943 , six studies included participants with compensated cirrhosis 36, 37, 42, 43, 50, 51 , and three studies included individuals with decompensated cirrhosis 33, 34, 38 . One study was excluded as it represented a population already included in another, more recent study; 52 one small RCT of statins in NASH was excluded due to insufficient information 53 .…”
Section: Resultsmentioning
confidence: 99%
“…Five studies reported risk of development of cirrhosis (or progression of fibrosis) in patients with baseline non-cirrhotic CLDs 35, 3941, 43 . In three studies, diagnosis of cirrhosis (or fibrosis progression) was ascertained based on a combination of administrative claims codes and calculated serum fibrosis markers (FIB-4 or APRI); one study was a post-hoc analysis of the HALT-C trial included patients with paired liver biopsies, with fibrosis progression defined based on increase in Ishak fibrosis stage by ≥ 2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Noninvasive methods had overcome the limitations of liver biopsy and were also used as prognostic indices for subjects with hepatitis B-associated HCC [39]. Furthermore, the accuracy of FIB-4 and APRI were 78% and 76% [40], suggesting they were suitable for regular monitoring of disease progression [41,42]. Thus, using APRI and FIB-4 to assess liver fibrosis was acceptable in the circumstances of the study.…”
Section: Discussionmentioning
confidence: 99%
“…Use of lipid lowering medications was inversely associated with LDL-C levels in both HCV/HIV co-infected and HIV monoinfected women, highlighting the effectiveness of these medications despite dysregulated lipid homeostasis. Furthermore, a recent study observed that statin use was associated with lower incidence of liver cirrhosis and hepatocellular carcinoma in HCV + veterans [47] . A future research priority will therefore be to define effects of recently-approved PCSK9 inhibitors – which have favorable toxicity and drug-drug interaction profiles as compared to statins - in HIV monoinfected and HCV/HIV co-infected women.…”
Section: Discussionmentioning
confidence: 99%